The Teaching Performance of the Mathematics Department for the Morning and Evening Studies in Light of the National Standards for Teacher Professional Development (A Comparative Study) - Jebur, Ayat Mohamed (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the research is to know and compare the reality of the teaching performance of students of the mathematics department for morning study and their peers for evening study in the light of national standards for teacher professional development The research followed the descriptive and analytical method, the sample consisted of )39(male and female students, a note card was designed out of (36) paragraphs and the research reached:There is a difference between the level of teaching performance of applied students in general at the level of significance (0.05) according to the note card. There is a difference between the level of teaching performance of students applying for morning study at the level of significance (0.05). There is a difference between the level of teaching performance of students applying for the evening study at the level of significance (0.05). There is no difference between the level of teaching performance of students applying for morning study and their peers for evening study at the level of significance (0.05). In light of the research results, a set of recommendations was developed.